Recombinant hemagglutinin displaying on yeast reshapes congenital lymphocyte subsets to prompt optimized systemic immune protection against avian influenza infection - Zhang, Han; Li, Zexing; Zhang, Huixia; Guo, Yanyu; Zhang, Xinyi; Zhang, Lilin; Yang, Liu; Li, Shujun; Li, Changyan; Cui, Daqing; Xie, Ruyu; Li, Yongqing; et al. (Frontiers in Microbiology, 2023)
Introduction Prophylactic vaccination is regarded as the most effective means to control avian flu infection. Currently, there is a need for a universal vaccine that provides broad and long-lasting protection against influenza virus. Meanwhile, although yeast-based vaccines have been used in clinic, studies are still required to further understand the molecular mechanism of yeast-based vaccines under physiological conditions. Methods We generated a yeast-based vaccine against influenza hemagglutinin (HA) of H5, H7 and H9 using surface displaying technology and evaluated the protective efficacy of chickens after exposure to H9N2 influenza virus. Results Oral yeast vaccine provided less clinical syndrome, reduced viral loading and alleviated airway damage significantly. Compared to the commercial inactivated vaccine, yeast vaccine stimulated the activation of splenic NK and APCs cells and boosted TLR7-IRF7-IFN signaling in spleen. Meanwhile, γδ T cells in the bursa of Fabricius were activated and the innate lymphoid cells (ILCs) in the bursa of Fabricius promoted the CILPs to differentiate to ILC3 cells in oral yeast birds. Moreover, the reshaped gut microbiota and a suppressed Th17-IL17-mediated inflammation in intestine was observed in oral yeast chickens, which might facilitate the recovery of intestinal mucosal immunity upon virus infection. Collectively, our findings suggest that oral yeast based multivalent bird flu vaccines provide an attractive strategy to update host defense function via reshapes of multi-systemic immune homeostasis.